Mergers and Acquisitions: - Almashal, Abdulrahman (2010)
Mergers and acquisitions (M&As) are booming a strategy of choice for organizations attempting to maintain a competitive advantage. Previous research on mergers and acquisitions declares that acquirers do not normally benefit from acquisitions. Targets, on the other hand, have a tendency of gaining positive returns in the few days surrounding merger announcements due to several characteristic on the acquisitions deal. The announcement period wealth effect on acquiring firms, however, is as clear as for targets. This dissertation, therefore, studies acquirer shareholders wealth impacts of large US firms that acquire public targets within a short time period, with alternative methods of payments between 2000 and 2005. Since acquirers pick different types of targets and methods of payment, any dissimilarity in returns must be due to the characteristics of the target and the bid. Results, in general, indicate that acquiring firms lose in purchasing public firms apart from acquirers finance their merger with cash. The results vary depending on the characteristics of the target and the bid. These results are consistent with a liquidity discount, and tax and control effects in this market.